2018
DOI: 10.33714/masteb.421047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tilia tomentosa methanolic extract on growth performance, digestive enzyme activity, immune response and haematological indices of common carp (Cyprinus carpio)

Abstract: A B S T R A C TThis study was conducted to determine the effect of dietary supplementation with Tilia tomentosa on the growth performance, digestive enzyme activity, haematological indices and nonspecific immune indices of juvenile common carp (Cyprinus carpio). Fish with an average weight of 4.35 ± 0.16 g were fed a diet supplemented with an aqueous methanolic extract of T. tomentosa at a dose of 0% (control), 0.01%, 0.05% or 0.1% for 45 days. The final weight, weight gain and specific growth rate were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…Regarding ORP, many researchers reported various results on the effects of medicinal plants. Almabrok et al (2018) Haematological responses are important determinants in fish health (Ahmed et al, 2020). In this study, RBC was increased CS-treated fish groups.…”
Section: Ta B L Ementioning
confidence: 63%
See 1 more Smart Citation
“…Regarding ORP, many researchers reported various results on the effects of medicinal plants. Almabrok et al (2018) Haematological responses are important determinants in fish health (Ahmed et al, 2020). In this study, RBC was increased CS-treated fish groups.…”
Section: Ta B L Ementioning
confidence: 63%
“…Hence, for prevention or treatment of diseases as well as reducing the effects of stress, the substances that are environment-friendly, economical in use, easily available and natural origins are worthy to use. In this respect, medicinal plants are being studied recently and often used (Almabrok et al, 2018;Karga et al, 2020;Mohamed et al, 2018;Sönmez, Bilen, Albayrak, et al, 2015;Sönmez et al, 2018;Zhu, 2020). Many studies demonstrated beneficial effects and indicated potential application of such herbal products (Arslan et al, 2018;Elbesthi et al,2020;Kesbiç et al, 2020;Parrino et al, 2020;Sönmez, Bilen, Alak, et al, 2015;Ümit et al, 2018;Yılmaz, 2017).…”
mentioning
confidence: 99%
“…In this study, MPO activity was significantly decreased in treated fish groups. Almabrok et al (2018) reported no difference in MPO activity in carp after treatment with linden (Tilia tomentosa). Contrarily, Mohamed et al (2018) found an increased activity of MPO in carp fed with Apium graveolens.…”
Section: Discussionmentioning
confidence: 99%
“…Almabrok et al. (2018) reported no difference in MPO activity in carp after treatment with linden ( Tilia tomentosa ). Contrarily, Mohamed et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although the highest final weight was recorded from BM2 fish group, this increase was not significant. The majority of studies on application of plant‐derived feed additives in fish observed enhanced (Akrami et al, 2015; Almabrok et al, 2018; Bilen, Altief, et al, 2020; Dada, 2019; Mohamed et al, 2018) or altered growth (Abdel‐Tawwab et al, 2015; Tan et al, 2018). No effect on growth of fish was also demonstrated (Bohlouli et al, 2016; Motamedi‐Tehrani et al, 2016; Peterson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%